A novel solder joints inspection method using curvature and geometry features in high-density flexible IC substrates surface mount technology. (25th November 2021) - Zeng, Yong; Hu, Yueming; Zhang, Xiaohan; Luo, Zhongliang; Wei, Xiaohui
Abstract: The automatic optical inspection based defective diagnosis systems in the surface-mounted device is fairly important to the optimization of electronic manufacturing. The gist of this paper is that presents a novel inspection system for the distinction of defective solder joints on the high-density flexible IC substrates. Initially, an ultra-high precision 3D information acquirement system is elaborated. Then, several critical sub-regions are divided and pivotal features are extracted from them, in which the differential geometry based estimation scheme to obtain discrete curvatures directly and the crest line representation based shape characterization method are proposed. Finally, each type of the solder joints is described with different and ordered feature sequences, and the practical classification process is formulated as the pattern recognition and classification problem, which is also implemented by the set of predefined diagnosis rules of thumb and the introduced logical operations. By classifying seven categories of industrial solder joints and exhaustively comparing with other state-of-the-art methods, the performances of the proposed diagnosis system is validated. Experimental results verify the effectiveness and efficiency of the developed system from three aspects, i.e. inspection speed, total correct rate, and detectable types.